2017
DOI: 10.1007/s12035-017-0513-7
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nitric Oxide Synthase Isoforms in Neurogenesis

Abstract: Nitric oxide (NO), a free radical gas, acts as a neurotransmitter or neuromodulator in the central nervous system (CNS). It has been widely explored as a mediator of neuroinflammation, neuronal damages, and neurodegeneration at its pathological levels. Recently, increasing evidence suggests that NO plays key roles in mediating adult neurogenesis, the process of neural stem cells (NSCs) to generate newborn neurons for replacing damaged neurons or maintaining the function of the brain. NO synthase (NOS) is a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…As such, 3DG can become a good drug carrier for those diseases due to its extra capacity to induce this enzyme's expression. Nitric oxide synthase is an oxidoreductase involved in various biological processes such as neurotransmission, amino acid metabolism, environmental signaling pathways, catabolism (Li et al, 2007;Naglah et al, 2016), the endocrine system, and smooth muscle motor control (Adams and Bronner-Fraser, 2009;Hillard, 2015), neuronal damages, neurodegeneration, and NSCs proliferation (Chong et al, 2018). L-amino acid oxidase is involved in the biosynthesis and metabolism of amino acids (Niedermann and Lerch, 1991), and we found that 3DG causes down-regulation of this enzyme in NSCs.…”
Section: Discussionmentioning
confidence: 75%
“…As such, 3DG can become a good drug carrier for those diseases due to its extra capacity to induce this enzyme's expression. Nitric oxide synthase is an oxidoreductase involved in various biological processes such as neurotransmission, amino acid metabolism, environmental signaling pathways, catabolism (Li et al, 2007;Naglah et al, 2016), the endocrine system, and smooth muscle motor control (Adams and Bronner-Fraser, 2009;Hillard, 2015), neuronal damages, neurodegeneration, and NSCs proliferation (Chong et al, 2018). L-amino acid oxidase is involved in the biosynthesis and metabolism of amino acids (Niedermann and Lerch, 1991), and we found that 3DG causes down-regulation of this enzyme in NSCs.…”
Section: Discussionmentioning
confidence: 75%
“…Growing empirical evidence indicates a unique role of NO in adult neurogenesis [70]. Accordingly, several agents have been successfully trialed with a rationale to increase brain NO levels, including arginine [71] and NO-donor supplementation [6].…”
Section: Discussionmentioning
confidence: 99%
“…NO is produced in the brain by neuronal NO synthase (nNOS) and serves as a key second messenger for instance, regulating neuronal plasticity and survival (Nakamura and Lipton, 2016; Chong et al, 2017). However, aberrant S-nitrosylation of proteins such as PDI and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) can occur in AD (Uehara et al, 2006; Zhao et al, 2015).…”
Section: Cysteines and Diseasesmentioning
confidence: 99%